New perspectives on the French presence in Bahia in 1798 - István Jancsó; Marco Morel; Eoin Paul O'Neill (Topoi)
The analysis of correspondence now avaiable on a Plan for the Invasion of Bahia, sent by naval captain Antoine-René Larcher to the Directorate of the French Republic in 1797, sheds new light on episodes of the so-called Bahian Conspiracy, as much with respect to the conspirators' social penetration as in regard to aspects of wideranging attempts to the expand the French Revolution previously unknown to historiography.